Pulse Coded Neural Network Implementation In VLSI - Shaikh-Husin, Nasir; Chang, Wooi Po (2000)
A neural network that encodes signals in terms of pulses has been designed and fabricated. The neural network components are described in detail. As a test case, a two-layer network is implemented. A preliminary test result shows some promise and some limitations of the design